SPRAY CHARACTERISTICS AND SPRAY-WALL IMPINGEMENT OF A DIESEL-CNG DUAL FUEL JET USING THE SCHLIEREN IMAGING TECHNIQUE - ISMAEL HARROUN, MHADI ABAKER (2013)
Natural gas for direct-injection (DI) compression ignition (CI) engines is considered to be the final optimized method due to its high volumetric efficiency, high thermal efficiency and low emissions. However, CNG has the penalty of high auto-ignition temperature and lower cetane number. An effective way to use CNG in CI engines is to inject the CNG with a pilot of diesel fuel for ignition purposes. In order to understand and control the injection and the jet characteristics, it is essential to understand how the gas jets assist the atomization of the pilot diesel spray and influence its characteristics as well as wall impingement.